1997
DOI: 10.1115/1.2831091
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Image Processing for Monitoring of Free Weld Pool Surface

Abstract: The arc weld pool is always deformed by plasma jet. In a previous study, a novel sensing mechanism was proposed to sense the free weld pool surface. The specular reflection of pulsed laser stripes from the mirror-like pool surface was captured by a CCD camera. The distorted laser stripes clearly depicted the 3D shape of the free pool surface. To monitor and control the welding process, the on-line acquisition of the reflection pattern is required. In this work, the captured image is analyzed to identify the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 5 publications
0
61
0
1
Order By: Relevance
“…The experimental results showed that this step had little influence on the result of image processing when using the developed algorithm in our system. Zhang and Kovacevic had also skipped this step [4,5]. Another reason to neglect this step is to improve the speed of the algorithm to meet the request of real-time.…”
Section: Noise Reduction and Image Enhancingmentioning
confidence: 99%
“…The experimental results showed that this step had little influence on the result of image processing when using the developed algorithm in our system. Zhang and Kovacevic had also skipped this step [4,5]. Another reason to neglect this step is to improve the speed of the algorithm to meet the request of real-time.…”
Section: Noise Reduction and Image Enhancingmentioning
confidence: 99%
“…Optical sensing techniques have been used for joint tracking and fill control, [5] weld pool width, and profile control. [6] Arc has also been used as a sensor in consumable and nonconsumable arc welding processes for joint tracking applications. [7] Ultrasonic sensing techniques have been developed to joint track and control weld pool penetration and geometry.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain 3D information of weld pool surface, Kovacevic et al [8], Kovacevic and Zhang [9] designed a suit of weld pool visual detection system, which is consist of strong pulse laser grid multi structure light strip and high-speed electronic shutter camera. The electronic shutter of camera synchronizes the laser pulse frequency.…”
Section: Introductionmentioning
confidence: 99%